Retinoic acid degradation shapes zonal development of vestibular organs and sensitivity to transient linear accelerations - Kazuya Ono (Nature Portfolio, 2020)
The coding of sensory inputs at the level of vestibular sensory organs is not well understood. In this study, the authors demonstrate that the formation of striolar/central zones during embryogenesis requires Cytochrome P450 26b1 (Cyp26b1)-mediated degradation of retinoic acid and show that Cyp26b1 cKO mice have abnormal vestibular evoked potentials and balance beam performance, but normal vestibular-ocular reflexes.